Nanoparticles loaded with IL-2 and TGF-β promote transplantation tolerance to alloantigen - Horwitz, David A.; Wang, Ju Hua; Kim, Dongin; Kang, Chang; Brion, Katja; Bickerton, Sean; La Cava, Antonio (Frontiers in Immunology, 2024)
We have previously reported that nanoparticles (NPs) loaded with IL-2 and TGF-β and targeted to T cells induced polyclonal T regulatory cells (Tregs) that protected mice from graft-versus-host disease (GvHD). Here we evaluated whether administration of these NPs during alloantigen immunization could prevent allograft rejection by converting immunogenic responses to tolerogenic ones. Using C57BL/6 mice and BALB/c mice as either donors or recipients of allogeneic splenocytes, we found that treatment with the tolerogenic NPs in both strains of mice resulted in a marked inhibition of mixed lymphocyte reaction (MLR) to donor cell alloantigen but not to third party control mouse cells after transfer of the allogeneic cells. The decreased alloreactivity associated with a 4-to 5-fold increase in the number of CD4 + and CD8 + T regulatory cells (Tregs) and the acquisition of a tolerogenic phenotype by recipient dendritic cells (DCs) in NP-treated mice. As allogeneic cells persisted in NP-treated mice, these findings suggest that tolerogenic NPs can induce alloantigen-specific Tregs and tolerogenic DCs promoting tolerogenic responses to alloantigen. By inhibiting reactivity to allotransplant, this approach could help reduce the need for immune suppression for the maintenance of allografts.